2008
DOI: 10.1111/j.1748-5827.2008.00583.x
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective study of canine D‐dimer concentrations measured using an immunometric “Point‐of‐Care” test

Abstract: The NycoCard D-dimer test card required no specialised equipment and could therefore facilitate rapid screening for thromboembolic disease/disseminated intravascular coagulation in first opinion practice. Elevations in D-dimer concentration can be found in a number of clinical conditions apart from thromboembolic disease/disseminated intravascular coagulation and should not therefore be used as the sole basis of diagnosis. D-dimer may be considered a good screening test for thromboembolic disease/disseminated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
38
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 12 publications
3
38
0
Order By: Relevance
“…In both dogs expressing FIX in the range of mild hemophilia (Wick and Trex), TAT complex and D-dimer levels at multiple time points remained in the normal range, 26,32 consistent with a lack of clinically recognized thrombosis (supplemental Figure 3). Notably, data from the dog Wiley showed continuous expression of supraphysiologic levels of FIX-Padua after inhibitor eradication for .400 days and yet presented no clinical evidence of peripheral thrombosis.…”
Section: Canine Studiesmentioning
confidence: 89%
See 1 more Smart Citation
“…In both dogs expressing FIX in the range of mild hemophilia (Wick and Trex), TAT complex and D-dimer levels at multiple time points remained in the normal range, 26,32 consistent with a lack of clinically recognized thrombosis (supplemental Figure 3). Notably, data from the dog Wiley showed continuous expression of supraphysiologic levels of FIX-Padua after inhibitor eradication for .400 days and yet presented no clinical evidence of peripheral thrombosis.…”
Section: Canine Studiesmentioning
confidence: 89%
“…24 Canine FIX antigen, activity, and antibody assays Whole blood clotting time (WBCT), cFIX antigen and activity, and thromboelastography (TEG) were assayed as previously described. 25,26 Neutralizing antibodies to cFIX were determined by the Bethesda assay. Antibodies against cFIX were measured by enzyme-linked immunosorbent assay (ELISA) against immunoglobulin (Ig)G1, IgG2, and total IgG (Bethyl Laboratories, Montgomery, TX).…”
Section: Systemic and Local Toxicitymentioning
confidence: 99%
“…Platelet counts were within the normal range throughout the study ( Figure 3A). Because mice continuously expressing mFVIIa at levels more than 2 g/mL exhibited premature mortality, 10 to further address the safety of this gene transfer approach, we used 3 different assays: levels of TAT complex, D-dimer levels (elevated levels of which are indicators of thromboembolic disease and disseminated intravascular coagulation [DIC] in dogs 29,30 ), and fibrinogen levels, elevated levels of which are associated with cardiovascular disease. 31 We did not detect any significant changes in TAT or D-dimer levels relative to pre-AAV administration (P Ͼ .2) in any of the vector doses used in AAV-treated dogs throughout the observation period ( Figure 3B and C, respectively).…”
Section: Safety Of Long-term Cfviia Expression In the Aav-treated Hemmentioning
confidence: 99%
“…A sensitivity of 100% with a specificity of 97% has been reported (Stokol et al 2000). An immunometric "Pointof-Care" test has been used in healthy dogs (Wiinberg et al 2007), dogs with chronic congestive heart failure (Tarnow et al 2007) and in clinically ill dogs with and without TE/DIC (Dewhurst et al 2008). In the latter study, D-dimer test was found to be an easy to use test, which could aid in a first opinion practice.…”
Section: Methods For D-dimer Determinationmentioning
confidence: 99%